1986
DOI: 10.1002/cne.902440105
|View full text |Cite
|
Sign up to set email alerts
|

A Golgi study of the neuronal population of the marginal zone (lamina I) of the rat spinal cord

Abstract: On the basis of dendroarchitecture and cell body shape, complemented with morphometry of dendritic ramification, four major neuronal types were distinguished in lamina I of the spinal cord of the rat. (I) Fusiform spiny cells (39% of impregnated neurons) have longitudinal spindle-shaped perikarya with bipolar, less frequently unipolar, dendritic trees rich in pedicled spines and a thin, beaded longitudinal axon; such neurons occur mainly in the lateral marginal zone. In type IA cells (33% of the total), the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
154
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 163 publications
(177 citation statements)
references
References 45 publications
22
154
1
Order By: Relevance
“…The dendrites could be followed easily for up to 400 m or more. Consistent with previous observations in rat, cat, and monkey (Gobel, 1978;Price et al, 1978;Beal et al, 1981;Lima and Coimbra, 1986;, CTb-labeled lamina I STT cells in the monkey arborize in the horizontal plane. Most cells were oriented longitudinally, and their primary dendritic arbors were nearly always restricted to lamina I; few cells were observed with a dendrite extending into lamina II.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The dendrites could be followed easily for up to 400 m or more. Consistent with previous observations in rat, cat, and monkey (Gobel, 1978;Price et al, 1978;Beal et al, 1981;Lima and Coimbra, 1986;, CTb-labeled lamina I STT cells in the monkey arborize in the horizontal plane. Most cells were oriented longitudinally, and their primary dendritic arbors were nearly always restricted to lamina I; few cells were observed with a dendrite extending into lamina II.…”
Section: Resultssupporting
confidence: 91%
“…First, previous retrograde labeling studies in cat and rat have produced conflicting results. Even though Golgi studies in cat (Gobel, 1978) and rat (Lima and Coimbra, 1986) both described similar cell types in lamina I (fusiform, pyramidal, and multipolar), a retrograde labeling study of lamina I STT cells in the rat reported that they were mostly pyramidal cells (Lima and Coimbra, 1988), whereas a comparable study in the cat found fusiform, pyramidal, and multipolar lamina I STT cells . Both studies utilized cholera toxin subunit b (CTb), which provides excellent retrograde morphological definition (Ericson and Blomqvist, 1988).…”
mentioning
confidence: 98%
“…The rest of the cells were next to the lateral edge of lamina I, among the superficial fibres of the DLF (n=18; cells 6-23) or within the LSN (n=9; cells 24-32). While neurons within lamina I could be classified according to the system introduced by Lima and Coimbra (1986), neurons located more laterally, outside the dorsal grey matter and in the LSN, with the exception of three cells (Table 1) presented very different somatodendritic features. We compared basic morphometric parameters of these neurons with a pooled sample of 3-D reconstructed PNs and LCNs (n=4 for each, L-I in Fig.…”
Section: General Somatodendritic Features Of Neurons Outside the Dorsmentioning
confidence: 99%
“…position soma / dendrite (Lima and Coimbra, 1986) midline Table 1 dorsolateral funiculus; DF, dorsal funiculus; L-I-X, lamina I-X; 3-D, neuron reconstructed in three-dimensions with Neurolucida; DCT, dorsal collateral type projection neuron (see Szucs et al, 2010); MCT, mixed collateral type projection neuron (see Szucs et al, 2010);…”
mentioning
confidence: 99%
“…Morphological and functional studies have revealed a tremendous diversity of dorsal horn neurons (Christensen and Perl, 1970;Lima and Coimbra, 1986;Todd and Spike, 1993;Han et al, 1998;Grudt and Perl, 2002;Todd and Koerber, 2006). Diversity of the dorsal horn neurons is further suggested by the expression of neuropeptides, including the opioid-like peptides Dynorphin (DYN) and enkephalin (ENK), the anti-opioid peptide cholecystokinin (CCK), the tachykinin peptides Substance P (SP) and Neurokinin B (NKB), somatostatin (SOM), and others (Marti et al, 1987;Todd and Spike, 1993;Todd and Koerber, 2006;Polgar et al, 2006).…”
Section: Introductionmentioning
confidence: 99%